Interdisciplinary approaches to human rights history, politics, practice - Srikanth, Rajini; Chowdhury, Elora Halim (Abingdon, Oxon Routledge, 2019)
"Interdisciplinary Approaches to Human Rights is an edited collection which brings together analyses of human rights work from multiple disciplines. Within the academic sphere, this book will garner interest from scholars who are invested in human rights as a field of study, as well as those who research and are engaged in the praxis of human rights. Referring to the historical and cross-cultural study of human rights, the volume engages with disciplinary debates in political philosophy, gender and women's studies, Global South/Third World studies, international relations, psychology, and anthropology. At the same time, the authors employ diverse methodologies including oral history, theoretical and discourse analysis, ethnography and literary and cinema studies. Within the field of human rights studies, this book attends to the critical academic gap on interdisciplinary and praxis-based approaches to the field, as opposed to a predominantly legalistic focus, drawing from case studies from a wide range of contexts in the Global South, including Australia, Bangladesh, Colombia, Haiti, India, Mexico, Palestine, and Sudan, as well as in the United States. For students who will go on to become researchers, practitioners, policy makers, and activists, this collection of essays will demonstrate the multifaceted landscape of human rights and the multiple forces (philosophical, political, cultural, economic, historical) that affect it"-- Provided by publisher.
Keywords: Human rights